(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
The study was designed to investigate the effect of cyclodextrins (CDs) on the solubility, dissolution rate, and bioavailability of cilostazol by forming inclusion complexes. Natural CDs like β-CD, γ-CD, and the hydrophilic β-CD derivatives, DM-β-CD and HP-β-CD, were used to prepare inclusion complexes with cilostazol. Phase solubility study was carried out and the stability constants were calculated assuming a 1:1 stoichiometry. Solid cilostazol complexes were prepared by coprecipitation and kneading methods and compared with physical mixtures of cilostazol and cyclodextrins. Prepared inclusion complexes were characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry (DSC), and X-ray diffraction (XRD) studies. In vitro dissolution study was performed using phosphate buffer pH 6.4, distilled water, and HCl buffer pH 1.2 as dissolution medium. The optimized inclusion complex was studied for its bioavailability in rabbit and the results were compared with those of pure cilostazol and Pletoz-50. Phase solubility study showed dramatic improvement in the solubility of drug by formation of complexes, which was further increased by pH adjustment. The in vivo study revealed that DM-β-CD increased the bioavailability of cilostazol with low variability in the absorption. Among all cilostazol–cyclodextrins complexes, cilostazol–DM-β-CD inclusion complex (1:3) prepared by coprecipitation method showed 1.53-fold and 4.11-fold increase in absorption along with 2.1-fold and 2.97-fold increase in dissolution rate in comparison with Pletoz-50 and pure cilostazol, respectively.